Pemberdayaan Masyarakat Miskin Melalui Pendidikan Kewirausahan Berbasis Teknologi Informasi Di Kecamatan Koto Tangah Kota Padang - Khairani Khairani; Rahmanelli Rahmanelli (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
Research conducted in Subdistrict Koto Tengah of Padang Cityis based on the number of people who have a weak economy with unemployment rate and the number of productive age is still high. The solution offered to overcome the high rate of poverty and improve the quality of life in Subdistrict Koto Tengah of Padang City is through entrepreneurship education based on information technology. In this case, research and dedication is done through workshops, skills training and business assistance. Based on the results of research and devotion, it can be known the ability of participants in making skills for entrepreneurship, that is by doing workshops and training, the ability of participants who viewed from the work of interesting experience increased, the change of paradigm thinking participants become more logical and analytical, which seen from the attitude of increasing enthusiasm for self-employment (independent), and the formation of new business groups that have high competitiveness and realible business. The next stage plan to be implemented is business assistance. Once the business group is established, each group that has been provided materials and tools will be accompanied by research and devotion teams, especially in marketing the products produced. Activities planned for the fourth week of October 2017 to market the training participants 'products are expected to help increase revenue from participants' work and reduce unemployment in Kecamatan Koto Tangah. Thus, participants whose activities have a high spirit and motivation in entrepreneurship can be helped.